Cluster-Based Modeling of Internal Factors and FinTech Influence on Strategy: A Case Study of Bank BNI - Aryandani, Aisyah; Firdaus, Asno Azzawagama (Mobile and Forensics, 2025)
The rapid development of financial technology (FinTech) and shifting organizational dynamics have compelled banking institutions to reassess their internal capabilities and strategic positioning. This study aims to examine the influence of internal factors namely the Core Values of State-Owned Enterprises (AKHLAK), innovation culture, gratitude, employee commitment, and employee performance on the competitive strategy of Bank BNI, while also investigating the moderating role of FinTech. A quantitative research design was employed using a survey method, involving 200 employees of Bank BNI. Data were analyzed using Cluster Analysis and Structural Equation Modeling–Partial Least Squares (SEM–PLS) through WarpPLS software. The results indicate that AKHLAK core values, innovation culture, and gratitude have significant positive effects on employee commitment and performance. Furthermore, both employee commitment and performance significantly enhance the bank’s competitive strategy. FinTech was found to significantly moderate the relationship between employee-related factors and competitive strategy. In conclusion, this study presents an integrated model that highlights the strategic role of internal organizational values and behavior, enhanced by digital technology, in fostering competitive advantage within the banking sector.